Strong association between the interleukin-8-251A/T polymorphism and coronary artery disease risk. Issue 10 (March 2019) - Wu, Ying; Wang, Wei; Li, Xiao-Yan; Qian, Ling-Ling; Dang, Shi-peng; Tang, Xu; Chen, Heng-Jian; Wang, Ru-Xing
Abstract : Abstract: Several reports have suggested a possible association between the interleukin (IL)-8-251A/T single-nucleotide polymorphism (SNP) and the susceptibility to coronary artery disease (CAD). Due to inconclusive results of the studies so far, we conducted a meta-analysis to systematically summarize the studies on the association between this SNP and CAD risk. A systematic literature search identified 9 case-control studies (3752 cases and 4219 controls) on the IL-8-251A/T polymorphism. We observed a significant association between different genetic forms of −251A/T SNP and CAD risk, like the allele model (A vs T: odds ratio [OR] 1.14, 95% confidence interval [CI] 1.02–1.27, P  = .02), dominant model (AA + AT vs TT: OR 1.20, 95% CI 1.01–1.43, P  = .042), recessive model (AA vs AT + TT: OR 1.15, 95% CI 1.03–1.27, P  = .01), and homozygous model (AA vs TT: OR 1.26, 95% CI 1.01–1.56, P  = .037), whereas the heterozygote model did not show any significant association (AT vs TT: OR 1.16, 95% CI 0.98–1.38, P  = .091). Furthermore, significant heterogeneity was observed among studies in terms of all genetic models, except the recessive model. Analysis of the ethnic subgroups revealed a significantly higher risk of CAD in the East Asian population carrying this SNP, and the heterogeneity among the studies regarding the East Asian population was decreased after subgroup analysis. The results of this meta-analysis suggest that the IL-8-251A/T SNP may increase the risk of CAD, especially in people of East Asian ethnicity. Further large-scale, multicenter epidemiological studies are warranted to validate this finding.